Biomaterial Influence on Intraocular Lens Performance: An Overview - Cari Pérez-Vives (Journal of Ophthalmology)
There is strong evidence that the IOL material is the factor having the greatest impact on posterior capsule opacification (PCO), anterior capsule opacification (ACO) development, and glistening formation after cataract surgery, even though there are other IOL features—such as haptic material and design and edge and optic design—that also have some influence. We reviewed the published literature describing the adverse events that are mainly related to the intraocular lens (IOL) material, such as PCO, ACO, and the subsequent capsule contraction, as well as glistening formation. The adverse events presented in this overview are the most common ones in clinical practice, and therefore, they are generally included in the clinical protocols for IOL evaluation.